Investigation of Factors Inhibiting Halal Certification in Micro and Small Industries (MSIs) of Meatball Product - Jauhari, Geovani Gita; Azizah, Siti; Al Awwaly, Khotibul Umam (PT. Riset Press International, 2025)
This study investigates the factors inhibiting halal certification among Micro and Small Industries (MSIs) of meatball products. Bondowoso Regency, as one of the regions in East Java Province, has good potential in developing micro and small-scale meatball industries. However, in reality, despite halal certification being legally mandated and crucial for consumer trust, especially in a country where the majority of the population is Muslim, no meatball MSIs in the region have obtained such certification. This study utilizes a qualitative methodology, incorporating interviews and triangulated data, to identify six inhibiting factors in halal certification for MSIs of meatball products. The following factors have been identified as contributing to the issue: 1) lack of socialization, 2) lack of knowledge of business actors on halal aspects of meatball products, 3) very high dependence of business actors on the existence of free halal certification, 4) lack of coordination between related institutions, 5) lack of human resources, and 6) lack of government role in mobilizing MSI actors to carry out halal certification. These findings underscore the need for strengthened collaboration among government, academia, and industry (triple helix) and more proactive regional strategies to meet the national halal certification target by 2026.